INVESTIGATION OF ZnO NANO STRUCTURES FABRICATED ON AL2O3 SUBSTRACTES BY MOCVD - Nguyen Thanh Binh; Vu Thi Bich; Y. Segawa (Universitas Gadjah Mada, 2007)
High quality ZnO nanostructures were grown directly on sapphire subtracts by metal organic vapor deposition. By changing the growth conditions, the different nano structures (nanorods,nanotubes, nanowalls, nanonetworks) can be selectively. These nanostructures were all epitaxially grown and had the same epitaxial relationship with respect to the substrate. Mechanisms corresponding to different nanostructures were discussed. The nanostructures exhibited stable excitonic states at room temperature, and the emission due to exciton-exciton scattering was observed